The Urgency of Islamic Business Ethics In The Era of The Industrial Revolution 4.0 - Havis Aravik; Makmun Harun; Rahma Febrianti (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
This article describes the urgency of business ethics in the era of the industrial revolution 4.0. The article is qualitative research in the type of literature research. This research is the analytical description and data analysis using the deductive thinking method. The study results showed that in the era of the industrial revolution 4.0. There are fundamental changes in various fields; one of them is the business field. For that, ethics is needed so the business can generate profits for all. Numerous Islamic business ethics are always relevant in business activities, such as honesty, selling goods according to quality, not using oaths, being loose and generous, building good relations between colleagues, orderly administration, and transparently setting the price is essential for business activities. So the business carried out produces peace and prosperity in the hearts and minds of business people. The corporation has to follow moral and religious values and does not break human principles.